Determinants of Restoration of CD4 and CD8 Cell Counts and Their Ratio in HIV-1–Positive Individuals With Sustained Virological Suppression on Antiretroviral Therapy. (1st March 2019) - Gras, Luuk; May, Margaret; Ryder, Lars Peter; Trickey, Adam; Helleberg, Marie; Obel, Niels; Thiebaut, Rodolphe; Guest, Jodie; Gill, John; Crane, Heidi; Dias Lima, Viviane; d'Arminio Monforte, Antonella; et al.
Abstract : Background: An increasing number of HIV-positive individuals now start antiretroviral therapy (ART) with high CD4 cell counts. We investigated whether this makes restoration of CD4 and CD8 cell counts and the CD4:CD8 ratio during virologically suppressive ART to median levels seen in HIV-uninfected individuals more likely and whether restoration depends on gender, age, and other individual characteristics. Methods: We determined median and quartile reference values for CD4 and CD8 cell counts and their ratio using cross-sectional data from 2309 HIV-negative individuals. We used longitudinal measurements of 60, 997 HIV-positive individuals from the Antiretroviral Therapy Cohort Collaboration in linear mixed-effects models. Results: When baseline CD4 cell counts were higher, higher long-term CD4 cell counts and CD4:CD8 ratios were reached. Highest long-term CD4 cell counts were observed in middle-aged individuals. During the first 2 years, median CD8 cell counts converged toward median reference values. However, changes were small thereafter and long-term CD8 cell count levels were higher than median reference values. Median 8-year CD8 cell counts were higher when ART was started with <250 CD4 cells/mm 3 . Median CD4:CD8 trajectories did not reach median reference values, even when ART was started at 500 cells/mm 3 . Discussion: Starting ART with a CD4 cell count of ≥500 cells/mm 3 makes reaching median reference CD4 cell counts more likely. However, median CD4:CD8 ratio trajectories remained below the median levels of HIV-negative individuals because of persisting high CD8 cell counts. To what extent these subnormal immunological responses affect specific clinical endpoints requires further investigation. Abstract : Supplemental Digital Content is Available in the Text.